Cognitive pediatric tele-assessment: a scoping review - Viñas-Guasch, Nestor; Chia, Phoebe Si Qi; Yap, Michelle Li-Mei; Wu, Chiao-Yi; Chen, S. H. Annabel (Frontiers in Psychology, 2023)
Cognitive tele-assessment (CTA) adoption has increased considerably recently, in parallel with the maturation of the digital technologies that enable it, and the push to move assessment to the online format during the Covid-19 pandemic in 2019. This mode of assessment stems from remote assessment applications that originated in general tele-medicine, where it was typically used for patient screening as part of an intervention. The development of remote tele-medicine was later adapted for CTA in adult populations in tele-neuropsychiatry and tele-psychology and is increasing applied in experimental research in cognitive science research with adult and pediatric populations, and for remote academic assessment. Compared to in-person assessment, CTA offers advantages such as decreasing time and logistic costs and facilitating the assessment of remote or special needs populations. However, given the novelty of CTA, its technical, methodological, and ethical issues remain poorly understood, especially in cases where methods for assessment of adults are used in pediatric populations. In the current paper, we provide a scoping review on the evolution of remote tele-assessment from the years 2000 to 2021, to identify its main themes, methodologies, and applications, and then focus on the issues of assessment in pediatric populations. Finally, we present recommendations on how to address the challenges previously mentioned.